Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1007/s12325-021-01972-8
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of the Meaningfulness of Symptom Reduction with Vibegron in Patients with Overactive Bladder: Analyses from EMPOWUR

Abstract: Introduction:Reductions in bothersome symptoms of overactive bladder (OAB) demonstrate improvement in clinical trials, but patient perception of meaningfulness of such

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…In an analysis of clinical meaningfulness of the EMPOWUR trial, significantly more patients receiving vibegron versus placebo achieved meaningful reductions in efficacy end points (ie, 15% reduction in micturitions, 50% reduction in urgency episodes, and 75% and 90% reduction in UUI episodes), which were associated with patient-perceived improvement. 18 Although slightly higher rates of certain TEAEs, such as headache, occurred more frequently with vibegron than with placebo among women (4.3% vs 2.6%, respectively), the incidence of headache with vibegron versus placebo aligns with the overall safety results of the overall population from the EMPOWUR trial (4.0% vs 2.4%, respectively). 16 In addition, TEAEs of hypertension in women displayed similar rates for vibegron and placebo (1.9% and 1.7%, respectively).…”
Section: N Original Researchmentioning
confidence: 69%
See 1 more Smart Citation
“…In an analysis of clinical meaningfulness of the EMPOWUR trial, significantly more patients receiving vibegron versus placebo achieved meaningful reductions in efficacy end points (ie, 15% reduction in micturitions, 50% reduction in urgency episodes, and 75% and 90% reduction in UUI episodes), which were associated with patient-perceived improvement. 18 Although slightly higher rates of certain TEAEs, such as headache, occurred more frequently with vibegron than with placebo among women (4.3% vs 2.6%, respectively), the incidence of headache with vibegron versus placebo aligns with the overall safety results of the overall population from the EMPOWUR trial (4.0% vs 2.4%, respectively). 16 In addition, TEAEs of hypertension in women displayed similar rates for vibegron and placebo (1.9% and 1.7%, respectively).…”
Section: N Original Researchmentioning
confidence: 69%
“…The LSMD for vibegron versus placebo was generally comparable in women and the overall population for micturitions (women, −0.5; overall, −0.5), UUI episodes (−0.7; −0.6), and urgency episodes (−0.8; −0.7). In an analysis of clinical meaningfulness of the EMPOWUR trial, significantly more patients receiving vibegron versus placebo achieved meaningful reductions in efficacy end points (ie, ≥15% reduction in micturitions, ≥50% reduction in urgency episodes, and ≥75% and 90% reduction in UUI episodes), which were associated with patient-perceived improvement 18 …”
Section: Discussionmentioning
confidence: 99%
“…Studies using the OAB-q and WPAI:US have shown that patients with OAB experience significantly decreased work productivity and HRQL, as well as impairment in daily activities, with significantly increased HCRU [ 3 , 4 , 35 ]. Vibegron has been shown to significantly improve QoL in patients with OAB in a clinically meaningful manner as reported by patients [ 36 , 37 ]. Improving QoL by mitigating bothersome symptoms of OAB in a real-world setting is a key component of COMPOSUR.…”
Section: Discussionmentioning
confidence: 95%
“…However, it is important to note that 24%−45% of patients receiving placebo in this analysis were classified as responders based on the various cut-off criteria. 27 When continuation rates were compared at 1 year with vibegron and mirabegron in a relatively small study with various populations, vibegron appeared superior (83.8% vs. 58.2%). 28 In those with idiopathic OAB (n = 56), it was 80% versus 42% in favor of vibegron.…”
Section: Beta-agonistsmentioning
confidence: 99%
“…In general, adverse event profiles were similar when compared to tolterodine for hypertension, UTI, nasopharyngitis, although dry mouth was better in favor of vibegron (1.8% vs. 5.2%) 26 . Frankel et al, in their study assessed the meaningfulness of these clinical reductions in endpoints using the patient perception of improvement 27 . They were able to demonstrate that significantly more patients treated with vibegron versus placebo achieved meaningful reductions in daytime frequency, urgency, and urge incontinence episodes.…”
Section: Beta‐3 Agonistsmentioning
confidence: 99%